(untitled) - Jalote, Pankaj (London, 2008)
Bibliography: 259 - 264; The Software Problem; Software Processes; Software Requirements Analysis and Speciï¬cation; Planning a Software Project; Software Architecture; Design; Coding and Unit Testing; Testing
Keywords: Software engineering; Công nghệ thông tin -- Kỹ thuật phần mềm